Tracking and predicting wood fibers processing with fluorescent carbohydrate binding modules. Issue 11 (3rd May 2017) - Hébert-Ouellet, Yannick; Meddeb-Mouelhi, Fatma; Khatri, Vinay; Cui, Li; Janse, Bernard; MacDonald, Kevin; Beauregard, Marc
Abstract : Fluorescent probes allow for quick analysis of wood fiber surface polysaccharides. Abstract : Wood fiber is a source of raw materials for established wood-based industries and for the nascent biofuel sector. Efficient processing of wood fiber polymers such as cellulose and hemicellulose requires close monitoring with methods such as FTIR, XPS or chemical analysis. Such methods are time-consuming and require the availability of specialized equipment and expertise. Recently, the carbohydrate recognition domains of glycohydrolases, known as carbohydrate binding modules, were used for studying the development and the biochemistry of plant cell walls. In this study, we engineered a series of color-coded fluorescent carbohydrate binding modules with specificities for four major carbohydrate fiber polymers. This approach allowed for quick, high-throughput analysis of fiber surface carbohydrates signatures and is herein used for monitoring and predicting the impact of various treatments on the strength properties of paper produced from such processed fibers. We believe that the simplicity of this environment-friendly approach could change the way industry optimizes wood fibers processing and deconstruction.